The Design of Applying Gamification in an Immersive Virtual Reality Virtual Laboratory for Powder-Bed Binder Jetting 3DP Training - Pai-Hsun Chen (MDPI AG, 2020)
The integration of Virtual Reality (VR) and gamification techniques can be used to produce a fun virtual laboratory, including virtual spaces and educational content. This study developed a prototype for a virtual laboratory for powder-bed binder jetting three-dimensional printing (3DP) training in universities. The 3DP virtual laboratory is expected to address problems encountered in teaching, training, and practicing with powder-bed binder jetting 3DP. The 3DP Training Virtual Laboratory was developed by using immersive VR technology to simulate two-handed operations. The user evaluation of the first version prototype revealed that the students lacked learning interest and motivation when using the prototype. Thus, gamification technology was integrated into the 3DP virtual laboratory prototype in the mid-implementation development phase. After refining and systematically developing the model to meet the modified requirements, user evaluations on the game elements showed positive feedback. This study concluded that elements of gamification design should be considered at the beginning of the educational or training system development in order to enhance students' motivation or engagement.